Vibratome Sectioning Mouse Retina to Prepare Photoreceptor Cultures - Clérin, Emmanuelle (J Vis Exp, 2014)
The retina is a part of the central nervous system that has organized architecture, with neurons in layers from the photoreceptors, both rods and cones in contact with the retinal pigmented epithelium in the most distant part on the retina considering the direction of light, and the ganglion cells in the most proximal distance. This architecture allows the isolation of the photoreceptor layer by vibratome sectioning. The dissected neural retina of a mouse aged 8 days is flat-embedded in 4% gelatin on top of a slice of 20% gelatin photoreceptor layer facing down. Using a vibratome and a double edged razor blade, the 100 µm thick inner retina is sectioned. This section contains the ganglion cells and the inner layer with notably the bipolar cells. An intermediary section of 15 µm is discarded before 200 µm of the outer retina containing the photoreceptors is recovered. The gelatin is removed by heating at 37 °C. Pieces of outer layer are incubated in 500 µl of Ringer's solution with 2 units of activated papain for 20 min at 37 °C. The reaction is stopped by adding 500 µl 10% fetal calf serum (FCS) in Dulbecco's Modified Eagle Medium (DMEM), then 25 units of DNAse I is added before centrifugation at RT, washed several times to remove serum and the cells are resuspended in 500 µl of DMEM and seeded at 1 x 10(5) cells/cm(2). The cells are grown to 5 days in vitro and their viability scored using live/dead assay. The purity of the culture is first determined by microscopic observation during the experiment. The purity is then validated by seeding and fixing cells on a histological slide and analyzing using a rabbit polyclonal anti-SAG, a photoreceptor marker and mouse monoclonal anti-RHO, a rod photoreceptor specific marker. Alternatively, the photoreceptor layer (97% rods) can be used for gene or protein expression analysis and for transplantation.